Employment Effects of Offshore Oil and Gas Regulations - Steven Payson; Brian W. Sloboda (Global Labor Organization (GLO), 2019)
The estimation of the employment effects of offshore safety and environmental regulation is often highly speculative and based on questionable assumptions. Nevertheless, it is still highly publicized and used as a basis for policy statements in support or, or in opposition to, proposed regulations. Much more reliable estimates of such employment effects can be made, however, based on fundamental principles of microeconomic analysis. This paper demonstrates this by developing a microeconomic model explaining the effects of offshore regulations on employment, assuming the standard profit-maximization behavior of firms. The paper finds that the most relevant and reliable measures of employment effects are: reductions in employment from operations that are terminated because of the new regulation, increases in employment because of additional labor needed to meet the new requirements, and increases in employment in equipment manufacturing when the regulation calls for the expanded use of certain equipment. The costs related to these contractions or expansions of employment can often be gleaned from information in the benefit-cost analysis that was required to accompany the proposed regulation by the regulatory agency involved. For example, the daily costs of offshore rigs and the costs of equipment can be translated to increases in employment.
Keywords: J23; D20; Q48; L51; 330; Offshore; Oil; Gas; Regulation; Employment; Microeconomics